CFD and Experimental Investigation of Dense Jet Interaction with Cross-Flows for Sustainable Coastal Outfall Design and Environmental Impact Mitigation - Taherian, Mostafa (Université d'Ottawa / University of Ottawa, 2025)
The scarcity and security of freshwater are becoming critical global concerns. Seawater reverse osmosis (SWRO) desalination is a promising solution to supply clean water sustainably; however, it produces hypersaline by-products that need to be safely disposed of in ambient environments. The direct discharge of dense effluents can lead to significant environmental issues, including water quality degradation and marine life disruption. A widely accepted method for mitigating these impacts is to use submerged offshore diffusers designed to rapidly dilute effluents to near-background levels, thus minimizing environmental harm. For an optimal design, it is essential to understand the influence of the ambient hydrodynamic forces and discharge characteristics on their performance. Realistic coastal environments are dynamic and dominated by flowing currents, turbulence, and shear, which complicate the interaction between buoyant discharges and cross-flow currents. This interaction, known as buoyant jet in cross-flow (JICF), highlights the need for accurate predictions of jet flow behavior and mixing while presenting considerable challenges. Therefore, a deeper understanding and more precise design guidelines for these outfalls are crucial. This thesis represents the first attempt to experimentally and numerically simulate dense discharges with various source inclinations, issuing perpendicular cross-flow currents with 3D trajectories. First, a comprehensive review of the developments and applications of buoyant JICFs and computational fluid dynamics (CFD) modeling of outfall discharges was conducted to identify existing knowledge gaps. The review revealed deficiencies in understanding the combined effects of different flowing current strengths and nozzle inclinations on the discharge performance, warranting further investigation. Although CFD methods for simulating outfall discharges have advanced, their application to buoyant JICFs is still in the early stages, presenting significant opportunities for further research. Second, laser-induced fluorescence (LIF) experiments were conducted to examine the effects of the flowing current strength and nozzle inclination on dense jets discharging perpendicular to the cross-flows. Nozzle angles of 30°, 45°, and 60° and various cross-flow Froude numbers (uᵣF, where uᵣ is the ratio of ambient cross-flow to jet velocity and F is the jet-densimetric Froude number) were studied to assess the 3D jet trajectories and concentration distributions. Empirical equations describing the jet dilution and geometrical characteristics were derived. The findings showed that the 60° jet achieved dilutions of over 50% and 20%, on average, more than those of the 30° and 45° jets, respectively, due to its longer trajectory and greater expansion. These results challenge previous reports that dilution is insensitive to nozzle angles between 40°-70° in stationary ambient water and highlight the 60° jet's sensitivity to changes in uᵣF compared to shallower angles. Third, a numerical study was conducted using the OpenFOAM finite-volume model. The accuracy of the model was verified by comparing the results from four Reynolds-averaged Navier-Stokes (RANS) simulations - standard k-ε, realizable k-ε, k-ω shear stress transport (SST), and Launder-Reece-Rodi (LRR) - with experimental data from the literature. The realizable k-ε and LRR schemes showed strong potential for simulating the flow behavior and dilution performance of dense JICFs due to their incorporation of realizability assumptions and Reynolds stress transport equations, respectively. In addition, the modeling approach successfully visualized the evolution of a time-averaged counter-rotating vortex pair (CRVP) along the jet trajectory. Fourth, the large eddy simulation (LES) modeling technique with OpenFOAM was used to reproduce our LIF experimental results for the 60° dense jets, which demonstrated superior mixing performance. Simulations were extended to a broader range of cross-flow Froude numbers, identifying three regimes: jet-dominated, regular cross-flow, and strong cross-flow-dominated. The LES results aligned well with the experimental data, confirming LES as a reliable method for capturing the complex flow behavior and dilution characteristics of dense JICFs. This research provides valuable insights for protecting coastal water bodies and improving the design and operational efficiency of submerged dense outfall systems. It underscores the importance of understanding the interaction between varying current strengths and discharge inclinations to optimize outfall performance in dynamic environments. Furthermore, the research discusses and highlights the capabilities of different CFD modeling approaches for outfall engineering design.
Keywords: Environmental Impact Mitigation; Sustainable Coastal Outfall Design; CFD and Experimental Investigation; Dense Jet; Cross-flows